Complete genome sequence of Mesorhizobium ciceri bv. biserrulae WSM1497, an efficient nitrogen-fixing microsymbiont of the forage legume Biserrula pelecinus - Rachel, J.; Haskett, T.; Ramsay, Joshua; Graham, W.; Terpolilli, J. (American Society for Microbiology, 2017)
We report here the complete genome sequence of Mesorhizobium ciceri bv. biserrulae strain WSM1497, the efficient nitrogen-fixing microsymbiont and commercial inoculant in Australia of the forage legume Biserrula pelecinus. The genome consists of 7.2 Mb distributed across a single chromosome (6.67 Mb) and a single plasmid (0.53 Mb).